A Straightforward Method for the Development of Positively Charged Gold Nanoparticle-Based Vectors for Effective siRNA Delivery - Tatiana N. Elizarova; Maxim L. Antopolsky; Denis O. Novichikhin; Artemiy M. Skirda; Alexey V. Orlov; Vera A. Bragina; Petr I. Nikitin (Molecules, 2023)
The therapeutic potential of short interfering RNA (siRNA) to treat many diseases that are incurable with traditional preparations is limited by the extensive metabolism of serum nucleases, low permeability through biological membrane barriers because of a negative charge, and endosomal trapping. Effective delivery vectors are required to overcome these challenges without causing unwanted side effects. Here, we present a relatively simple synthetic protocol to obtain positively charged gold nanoparticles (AuNPs) with narrow size distribution and the surface modified with Tat-related cell-penetrating peptide. The AuNPs were characterized using TEM and the localized surface plasmon resonance technique. The synthesized AuNPs showed low toxicity in experiments in vitro and were able to effectively form complexes with double-stranded siRNA. The obtained delivery vehicles were used for intracellular delivery of siRNA in an ARPE-19 cell line transfected with secreted embryonic alkaline phosphatase (SEAP). The delivered oligonucleotide remained intact and caused a significant knockdown effect on SEAP cell production. The developed material could be useful for delivery of negatively charged macromolecules, such as antisense oligonucleotides and various RNAs, particularly for retinal pigment epithelial cell drug delivery.